The firm size effect: Fact or artifact? - John Ekberg; Mickael Salabasis (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
The size-wage effect is well documented in the empirical literature, and typical attempts of explanation center on the supply side, using variations of the human capital approach, perhaps combined with institutional theories. With conclusive evidence of its source yet to emerge, an alternative approach with interesting prospects attempts to give the demand side a more active part to play. Interpreting jobs as tasks, potentially firm-specific and organized in hierarchies, the optimal position for an individual can be assumed to be a function of ability and human capital, while the wage for a specific task is primarily decided by its value for the firm. Then, the role played by human capital changes, its effect being only indirect on wages, and the issue of how the existence of task structures, or career ladders, affect wages becomes paramount. Using data with detailed information about job content and structure, evidence of a natural positive correlation between size and structure is found. Combined with the reasonable assumption of a positive correlation between the position of tasks in the hierarchy and the wage, a size effect may very well come out positive and significant if we fail to control for it, making it an artifact of the data rather than an accurate description of the world.
Keywords: J31; J41; J44; 330; wages; plant size; occupational hierarchies; Lohn; Betriebsgröße; Schätzung; Schweden